2019
DOI: 10.1038/s41467-019-13086-5
|View full text |Cite
|
Sign up to set email alerts
|

eIF4A supports an oncogenic translation program in pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy with limited treatment options. Although metabolic reprogramming is a hallmark of many cancers, including PDA, previous attempts to target metabolic changes therapeutically have been stymied by drug toxicity and tumour cell plasticity. Here, we show that PDA cells engage an eIF4F-dependent translation program that supports redox and central carbon metabolism. Inhibition of the eIF4F subunit, eIF4A, using the synthetic rocaglate CR-1-31-B (CR-31) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 70 publications
13
88
5
Order By: Relevance
“…So far, no published data on the pharmacokinetic properties of CR-31-B (−) are available. It was already shown that daily intraperitoneal injection of CR-31-B (−) works well in mice (Wolfe et al, 2014;Chan et al, 2019) while the systemic availability of rocaglates following oral application seems to be limited (Saradhi et al, 2011). Based on this and our own data, we conclude that CR-31-B (−) may represent an interesting alternative to the broad-spectrum antiviral Silvestrol, which remains to be confirmed in appropriate in vivo studies to evaluate and compare the antiviral potential, toxicity and pharmacokinetics profiles of the two compounds.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no published data on the pharmacokinetic properties of CR-31-B (−) are available. It was already shown that daily intraperitoneal injection of CR-31-B (−) works well in mice (Wolfe et al, 2014;Chan et al, 2019) while the systemic availability of rocaglates following oral application seems to be limited (Saradhi et al, 2011). Based on this and our own data, we conclude that CR-31-B (−) may represent an interesting alternative to the broad-spectrum antiviral Silvestrol, which remains to be confirmed in appropriate in vivo studies to evaluate and compare the antiviral potential, toxicity and pharmacokinetics profiles of the two compounds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the upregulation of eIF4E functions as an effective indicator for ~30% of all cancer cases tested, and the phosphorylation of eIF4E promotes cellular proliferation and inhibits apoptosis (12). eIF4A2 was the focus of the present study, and is a subunit of eIF4A that is associated with the oncogenic translation of PDA (24). eIF4A is a subunit of eIF4F that also comprises eIF4E (a cap binding protein) and eIF4G (a regulatory scaffold protein).…”
Section: Discussionmentioning
confidence: 95%
“…Biologically identified as an ATP-dependent RNA helicase, eIF4A2 belongs to the eukaryotic initiation factor (eIF) family, which is essential for translation initiation (30). Existing findings have established various associations between the eIFs and carcinogenesis, as well as patient prognosis (11,13,24). For example, the upregulation of eIF4E functions as an effective indicator for ~30% of all cancer cases tested, and the phosphorylation of eIF4E promotes cellular proliferation and inhibits apoptosis (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we noticed that all SGs nucleators (TIA-1, TIAR, G3BP1, G3BP2, and CAPRIN-1) have an “enhancing” effect on cancer development properties [ 62 , 64 , 65 , 66 , 67 , 68 , 71 , 72 , 73 ], whereas USP10, a SGs inhibitor, has anti-cancer properties [ 74 , 75 ] ( Figure 5 ). There are some interesting correlation between other SGs markers and development, such as eIF3s and eIF4s subunits and complexes, UBAP2L or YB1, for example [ 138 , 155 , 156 , 157 , 158 , 159 , 160 ]. All of those proteins have, in common, to be recruited to SGs or to have role in their regulation [ 31 , 138 , 161 , 162 ].…”
Section: Perspectivesmentioning
confidence: 99%